2022
DOI: 10.1186/s13613-022-01004-w
|View full text |Cite
|
Sign up to set email alerts
|

Effects of regional citrate anticoagulation on thrombin generation, fibrinolysis and platelet function in critically ill patients receiving continuous renal replacement therapy for acute kidney injury: a prospective study

Abstract: Background Regional citrate anticoagulation (RCA) is recommended for continuous renal replacement therapy (CRRT). However, filter life varies and premature filter clotting can occur. The aims of this explorative prospective study were to investigate the effects of RCA on thrombin generation, fibrinolysis and platelet function in critically ill patients receiving CRRT, to compare clotting parameters between systemic and intra-circuit blood samples, and to screen participants for coagulation diso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
1
4
0
1
Order By: Relevance
“…This important pro-inflammatory reaction, as expected, activates the coagulation response: platelets are in the lower normal range, PAI-1 is increased, and TEG analysis showed high or normal MA in more of 50% of patients, confirming that hypercogulation is a common trait during sepsis [14].…”
Section: Tablesupporting
confidence: 73%
See 1 more Smart Citation
“…This important pro-inflammatory reaction, as expected, activates the coagulation response: platelets are in the lower normal range, PAI-1 is increased, and TEG analysis showed high or normal MA in more of 50% of patients, confirming that hypercogulation is a common trait during sepsis [14].…”
Section: Tablesupporting
confidence: 73%
“…Finally, histones and other dams or pumps are strongly adsorbed by heparin layers, which may be early saturated and then inhibited to anticoagulate the membrane [18]. Thus, citrate protocol we used in this study seems a rational alternative to heparin [14].…”
Section: Tablementioning
confidence: 99%
“…They showed significant decreased levels of MPO and IL-8 in the RCA group compared to the heparin group. Fisher et al [26] explored other coagulation parameters on fibrinogen, D-dimer, thrombin generation assay, and platelet function assay. Results showed that RCA did not affect thrombin generation, D-dimer function, or platelet function.…”
Section: Discussionmentioning
confidence: 99%
“…The major complications of citrate anticoagulation include citrate accumulation, hypocalcaemia, hypernatraemia, and metabolic acid–base disorders [26]. Citrate affects systemic coagulation, and there have been few reports of bleeding induced by citrate anticoagulation [27]. The ideal state of anticoagulation in CRRT is to achieve a good anticoagulation effect without associated complications.…”
Section: Discussionmentioning
confidence: 99%